The initial resuscitation of septic shock - GÜL, FETHİ; CİNEL, İSMAİL HAKKI (W B SAUNDERS CO-ELSEVIER INC, 2020)
Septic shock is the most severe form of sepsis, characterized by (a) persistent hypotension despite fluid resuscitation and (b) the presence of tissue hypoperfusion. Delays in the diagnosis and initiation of treatment of septic shock is associated with increasing risk for mortality. Early and effective fluid resuscitation and vasopressor administration play a crucial role in maintaining tissue perfusion in septic shock patients. A low diastolic arterial pressure (DAP) correlates with severity of arteriolar vasodilation, compromises left ventricle oxygen supply and can be used for identifying septic shock patients thatwould potentially benefit fromearlier vasopressor therapy. Controversy currently exists as to the balance of fluids and vasopressors to maintain target mean arterial pressure. The aim of this article is to review the rationale for fluid resuscitation and vasopressor therapy and the importance of both mean and diastolic blood pressure during the initial resuscitation of the septic shock. We relate our personal prescription of balancing fluids and vasopressors in the resuscitation of septic shock. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: Sepsis; Septic shock; Vasopressors; Fluid resuscitation; Diastolic blood pressure; Mean arterial pressure; GOAL-DIRECTED THERAPY; INTERNATIONAL CONSENSUS DEFINITIONS; TRIAL SEQUENTIAL-ANALYSIS; CRITICALLY-ILL PATIENTS; SEVERE SEPSIS; FLUID RESUSCITATION; CRITICAL ILLNESS; BLOOD-PRESSURE; VENOUS RETURN; NOREPINEPHRINE